6(4y+5z)-30z=

Simple and best practice solution for 6(4y+5z)-30z= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(4y+5z)-30z= equation:


Simplifying
6(4y + 5z) + -30z = 0
(4y * 6 + 5z * 6) + -30z = 0
(24y + 30z) + -30z = 0

Combine like terms: 30z + -30z = 0
24y + 0 = 0
24y = 0

Solving
24y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Divide each side by '24'.
y = 0

Simplifying
y = 0

See similar equations:

| 4log(x-6)=11 | | 16h-13h-2h-1=15 | | (25.12^2)/4(3.14) | | 52=12+4w | | -7/9(x-y+36) | | 2c-c=14 | | (80x-54y)-(62x+9y)= | | 8y-y+2y=18 | | 5(2y+4z)-20z= | | 15+3y=25 | | 4x-5/3x | | 6y(3y-4)+22y= | | (11x+23y)+(38x+50y)= | | -(2x^2-7x+7)= | | 4y(3y-6)+19y= | | A=8*(3.14) | | 4x-6=4(x+5) | | (63x+45y)-(13x+40y)= | | 6(x-6)+20=2(x-6) | | -(12b-10)+5(3b-2)= | | 8x+3=-3+3x+21 | | (23x+64y)+(33x-16y)= | | 4a-2(a+6)= | | a/3=7/10 | | (43x+60y)+(38x-23y)= | | (79x+76y)-(16x+40y)= | | -3x-13=6x+23 | | 16/b=2/3 | | y+3y+2y=12 | | 7a-4(a+6)= | | 6(2y+3z)-18z= | | 9=9x-36 |

Equations solver categories